Elements of Creative Writing - Schraffenberger, J.D; Morgan, Rachel; Tracey, Grant (Open textbook library., 2023)
This free and open access textbook introduces new writers to some basic elements of the craft of creative writing in the genres of fiction, poetry, and creative nonfiction. The authors—Rachel Morgan, Jeremy Schraffenberger, and Grant Tracey—are editors of the North American Review, the oldest and one of the most well-regarded literary magazines in the United States. They’ve selected nearly all of the readings and examples (more than 60) from writing that has appeared in NAR pages over the years. Because they had a hand in publishing these pieces originally, their perspective as editors permeates this book. As such, they hope that even seasoned writers might gain insight into the aesthetics of the magazine as they analyze and discuss some reasons this work is so remarkable—and therefore teachable. This project was supported by NAR staff and funded via the UNI Textbook Equity Mini-Grant Program.